Diagnosis of the Foreign Direct Investment Landscape in India - Fernandez, Manuel; Joseph, Robinson; Fernandez, Vania Maria (International Journal of Economics and Financial Issues, 2022)
There is a great flow of funds among countries, money flowing to more attractive destinations than others. Investors prefer to invest in destinations that offer attractive returns and are relatively less risky. FDI gives access to capital that would otherwise be not available, and provides much-needed foreign exchange, and therefore helps to adjust some of the macroeconomic imbalances in developing countries. India is in the growth mode, trying to boost the growth rate, but the resources available are limited; hence India is competing against others to make the investment climate more investor-friendly. This study aims to find out the status of India as an FDI destination, the factors that attract and hinder the inflow of FDI, and how to capitalize on them. This study is based on secondary data and covers a period of five years. The study analysis various determinants of FDI and reveals that India has the potential, decent growth, political stability, organized financial system and acceptable policy that makes it attractive to FDI.